POLITIK HUKUM OTONOMI DESA BERDASARKAN UNDANG-UNDANG NOMOR 6 TAHUN 2014 TENTANG DESA - Firdaus, Emilda; Indra, Mexsasai (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Village setting during this applies is no longer appropriate with the times, especially concern problem the position of customary law community, democracy and equitable development, Cousing the gap between regions which can interfere the integrity of the country. After the enactment of Law No. 6 2014 about the village, the position and authority of the village is based on the principle of autonomy that leads to the village form of independence. The principle above referred to the recognition principle and subsidiarity. Village honored in full by the supra-village as a legal entity, which was given the authority to megambil policy in the locality scale.The problems in this research are How legal political setting about the village by statute No.6 2014 about the village. How The Position of Village by statute No.6 2014 about the village. This study uses a type of normative juridical approach or also called doctrinal legal research. Called doctrinal legal research because research is done or directed only at the written regulations or materials other law. Methods and means of collecting legal materials is to use secondary data, that is data that has been established by previous researchers, or often referred to as a legal matter, the primary legal materials, secondary and tertiary.From the research results,that Law No.6 2014 about the village has given more power autonomy from the previous rules, that the village can the organization of village based culture and authenticity of the village without the intervention from government there on top. The position of village in this rules still be District or Town but the village not anymore is subordinate from District or Town. Village to District or Town only limited report responsibility the organization of village.Keywords : Political Law, Autonomy, The Village, Law No. 6 /2014